2020
DOI: 10.3390/math8030312
|View full text |Cite
|
Sign up to set email alerts
|

Novel Face Index for Benzenoid Hydrocarbons

Abstract: A novel topological index, the face index ( F I ), is proposed in this paper. For a molecular graph G, face index is defined as F I ( G ) = ∑ f ∈ F ( G ) d ( f ) = ∑ v ∼ f , f ∈ F ( G ) d ( v ) , where d ( v ) is the degree of the vertex v. The index is very easy to calculate and improved the previously discussed correlation models for π - e l e c t r o n energy and boiling point of benzenoid hydrocarbons. The study shows that the multiple linear regression involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In [14], using multiple linear regression, it has been shown that the novel face index can predict the π electron energy and boiling point of benzenoid hydrocarbon with a correlation coefficient greater than 0.99. erefore, this index can be useful in QSPR/QSAR studies. In this paper, we have computed the novel face index of some nanotubes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [14], using multiple linear regression, it has been shown that the novel face index can predict the π electron energy and boiling point of benzenoid hydrocarbon with a correlation coefficient greater than 0.99. erefore, this index can be useful in QSPR/QSAR studies. In this paper, we have computed the novel face index of some nanotubes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Jamil et al [14] introduced a novel topological index named as the face index. e face index helped to predict the energy and the boiling points of selected benzenoid hydrocarbons with the correlation coefficient r > 0.99.…”
Section: Introductionmentioning
confidence: 99%
“…In Jamil et al [27], the authors introduced a new TI, which is named as face index (FI) and is defined as FI()G=fF()Gd()f=vf,fF()Gd()v where G is a planer graph and vf represents the vertex v, incident on face f and F()G is set of all faces of G. For the computation of FI, we partition the graph into its faces.…”
Section: Introductionmentioning
confidence: 99%
“…For the notions and notations not given here, we refer [16] to the readers. Recently, Jamil et al [17] introduced a novel topological index named as the face index. ey showed that the face index can help to predict the boiling points and the energy of selected benzenoid hydrocarbons with the correlation coefficient r > 0.99.…”
Section: Introductionmentioning
confidence: 99%